Heat susceptibility of aquatic mycobacteria. - Schulze-Röbbecke, R (1992)
An investigation was carried out to measure the heat susceptibility of opportunistic mycobacteria frequently isolated from domestic water supply systems. The study was conducted under standardized conditions designed to resemble those found in oligotrophic aquatic habitats. Strains of the following species were tested: Mycobacterium avium, M. chelonae, M. fortuitum, M. intracellulare, M. kansasii (two strains), M. marinum, M. phlei, M. scrofulaceum, and M. xenopi. Suspensions of the test strains were exposed to temperatures of 50, 55, 60, and 70 degrees C; samples were taken at defined intervals to determine the concentration of survivors. From these data, the decimal reduction times were calculated for each test strain and test temperature. The results indicate that M. kansasii is more susceptible to heat than Legionella pneumophila, whereas the heat susceptibilities of M. fortuitum, M. intracellulare, and M. marinum lie in the same order of magnitude as that of L. pneumophila. The strains of M. avium, M. chelonae, M. phlei, M. scrofulaceum, and M. xenopi were found to be more thermoresistant than L. pneumophila, with the highest resistance being found in M. xenopi. Thermal measures to control L. pneumophila may therefore not be sufficient to control the last five mycobacterial species in contaminated water systems.